2015
DOI: 10.1038/srep14046
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of regulatory T cell induction by immunomodulatory herbal medicine licorice and its two constituents

Abstract: Regulatory T cells (Treg) play a critical role to control immune responses and to prevent autoimmunity, thus selective increase of Treg cells in vivo has broad therapeutic implications for autoimmune and inflammatory diseases. Licorice is a well-known herbal medicine used worldwide for over thousands of years, and accumulating evidence has shown its immunomodulatory potential. However, it is not clear whether licorice could regulate the induction and function of Treg cells. Here we found licorice extract could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…Its biological activities include anti-allergic 20 , anti-angiogenesis 21 , and anti-tumor growth 22 . A recent paper showed that ILG promotes regulatory T cell differentiation 23 . We reported previously that ILG suppressed LPS-TLR4/MD-2 complex signaling at the receptor level, resulting in inhibition of NF-κB and MAP kinases activation 24 .…”
mentioning
confidence: 99%
“…Its biological activities include anti-allergic 20 , anti-angiogenesis 21 , and anti-tumor growth 22 . A recent paper showed that ILG promotes regulatory T cell differentiation 23 . We reported previously that ILG suppressed LPS-TLR4/MD-2 complex signaling at the receptor level, resulting in inhibition of NF-κB and MAP kinases activation 24 .…”
mentioning
confidence: 99%
“…LE had no effect on the spleen index and kidney index of weaned piglets (Table 1). Studies shown that licorice extract mainly affects liver and intestine of weaned piglets [20,31].…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-2/Bax family of genes, which are the regulatory factors for apoptosis, were found to be modulated by the components of GL root, and can be considered in elucidation of its reported cytoprotective action. Licorice contains two chemical components, isoliquiritigenin and naringenin, which have been reported to enhance regulatory T cells and therefore may be cause of the anti-inflammatory properties and efficacy against autoimmune diseases [96]. Dorhoi et al [97] induced enhanced cellular immunity in birds treated with the ethanol extracts of licorice.…”
Section: Glycyrrhiza Glabra (Licorice or Sweetwoods)mentioning
confidence: 99%